Sustainable solutions for Cr6+ removal using carbon-based adsorbents - Perluxo, Julia D.; Alves, Fillip Cortat [UNESP]; Maia, Lana S.; Faria, Maria Ismênia S.T.; de Oliveira, Daniel M.; Botelho, Edson Cocchieri [UNESP]; Rosa, Derval S.; Mulinari, Daniella R. (Elsevier, 2025)
Removing potentially toxic elements (PTEs), such as hexavalent chromium (Cr6+), from water presents a significant challenge, especially given the increasing global demand for potable water. This study evaluated the effectiveness of three carbon-based structures — graphene, printex, and biomass-derived biochar — for Cr6+ adsorption in water, aiming to identify efficient and sustainable solutions for wastewater treatment. To investigate the influence of different carbon-based structures on Cr6+ adsorption, the physical, chemical, morphological, and thermal properties, as well as particle sizes, were evaluated. Adsorption experiments were conducted under varying conditions of contact time, initial Cr6+ concentration, and adsorbent dosage, with responses optimized through response surface methodology. Additionally, a Life Cycle Assessment (LCA) was conducted to evaluate the environmental impacts of the developed process, providing a broader sustainability perspective compared to conventional methods. Results indicated significant adsorption efficiencies for all materials: biochar achieved 85.1 % removal of Cr6+ under optimal conditions (using a 100 mg dosage, at a concentration of 1 mmol.L−1, over 30 min of contact time); Printex reached 85.4 %, and graphene recorded the highest removal rate at 89 %. Adsorption isotherms were best described by the Langmuir model, with maximum capacities of 67.7 mg g⁻¹ for graphene, 30.4 mg·g⁻¹ for Printex, and 13.3 mg·g⁻¹ for biochar. The structural properties of each material influenced this difference in adsorption capacity. The layered structure of graphene and the rough morphology of printex contributed to its performance, while the porous morphology and surface functional groups of biochar also favored adsorption. Nevertheless, this study identifies biochar as a promising and cost-effective material derived from biomass waste, aligning with sustainability goals. The proposed LCA scenarios reinforce this advantage, demonstrating reduced environmental impacts — particularly in terms of human toxicity and aquatic ecotoxicity — and benefits from a circular economic perspective. Importantly, this work provides a direct and systematic comparison of three commonly used carbon-based materials under identical experimental conditions, thereby addressing a key gap in literature and guiding more effective selection of adsorbents for environmental applications.